2017
DOI: 10.1007/s11694-016-9455-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative physico-chemical, functional and structural characteristics of winged bean [Psophocarpus tetragonolobus DC] and Soybean [Glycine max.] Protein isolates

Abstract: The physicochemical (colour, bulk density, thermal properties, molecular sizes), functional (water and oil absorption, solubility, emulsifying and gelation properties) and secondary structural properties of winged bean isolate (W-ISO) were studied and compared with those of soybean isolate(S-ISO) as reference. Results showed that W-ISO and S-ISO had extraction rates of 32.23 and 37.52 g/100 g, respectively, with corresponding protein content of 81.68 and 85.69% (dry weight basis). W-ISO and S-ISO had denaturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 71 publications
4
10
0
Order By: Relevance
“…() reported 1.32, 1.19, 1.26, 1.30, 1.14, and 1.12 g/g OHC for whole pinto, pink, Great Northern, dark red kidney, light red kidney, and small white bean flours, respectively, which are comparable to the OHC of the beans in our study. Additionally, several dry beans have been reported to have OHC values in the same range (1 to 2 g/g) as in our investigation (Adebowale & Lawal, ; Aguilera et al., ; Ai et al., ; Appiah et al., ; Du et al., ), as do certain oilseeds, including soybean (Agume, Njintang, & Mbofung, ; Makeri et al., ; Padilla, Alvarez, & Alfaro, ), lupine (Sathe, Deshpande, & Salunkhe, ), and winged bean (Makeri et al., ; Sathe, Deshpande, & Salunkhe, ). OHC found in our investigation (0.96 g/g) for soybean flour was comparable to that reported by Lin, Humbert, and Sosulski (), 84.4% (that is, 0.84 g/g) and higher than the reported oil absorption capacity for defatted soy flour, 29.59% (that is, 0.29 g/g) reported by Padilla et al.…”
Section: Resultssupporting
confidence: 78%
“…() reported 1.32, 1.19, 1.26, 1.30, 1.14, and 1.12 g/g OHC for whole pinto, pink, Great Northern, dark red kidney, light red kidney, and small white bean flours, respectively, which are comparable to the OHC of the beans in our study. Additionally, several dry beans have been reported to have OHC values in the same range (1 to 2 g/g) as in our investigation (Adebowale & Lawal, ; Aguilera et al., ; Ai et al., ; Appiah et al., ; Du et al., ), as do certain oilseeds, including soybean (Agume, Njintang, & Mbofung, ; Makeri et al., ; Padilla, Alvarez, & Alfaro, ), lupine (Sathe, Deshpande, & Salunkhe, ), and winged bean (Makeri et al., ; Sathe, Deshpande, & Salunkhe, ). OHC found in our investigation (0.96 g/g) for soybean flour was comparable to that reported by Lin, Humbert, and Sosulski (), 84.4% (that is, 0.84 g/g) and higher than the reported oil absorption capacity for defatted soy flour, 29.59% (that is, 0.29 g/g) reported by Padilla et al.…”
Section: Resultssupporting
confidence: 78%
“…In the present study, crude protein content ranged from 40.30% (Tpt17) to 38.88% (Tpt4) for processed seeds and 31.13% in Tpt17 to 28.43% (Tpt125) which are higher than results previously obtained for cowpea (22.5%), pigeon pea (22.4%), and lima beans (23.3%) but similar to the results for soybeans (35%) [11][12][13]. e values were also higher than the 14.70% [14] and 12.86% [15] previously reported for wheat flour.…”
Section: Discussionsupporting
confidence: 83%
“…Considering that most of these ANFs are destroyed by boiling or autoclaving [34], properly processed winged bean can be safely used as a major plant protein source. Overall, the proximate and antinutritional assessments of winged bean seeds and tubers were similar to those of previous studies of the crop and other similar crops [12,19,21,[44][45][46][47].…”
Section: Discussionsupporting
confidence: 83%
“…High EE contents of soybean, winged bean, rubber seed, and tropical almond observed in the present study were in agreement with some other reports [ 7 - 9 ]. Winged bean apparently contains CP comparable or even higher than that of soybean.…”
Section: Discussionsupporting
confidence: 94%
“…Winged bean ( Psophocarpus tetragonolobus ), rubber seed ( Hevea brasiliensis ), and tropical almond ( Terminalia catappa ) are protein-rich materials and grow abundantly in tropical regions. A number of previous studies have reported the protein contents of winged bean, rubber seed, and tropical almond, i.e., 40.3, 21.9, and 20.1% DM, respectively [ 7 - 9 ], and the values were generally lower in comparison to soybean except for winged bean. These materials also contain substantial amounts of lipids that may hamper rumen degradation and fermentation when present in excessive amount in the rumen, particularly due to negative effects of lipids on population and activity of cellulolytic microbes [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%